Large‐scale siting of sand dams: A participatory approach and application in Angolan drylands. (1st November 2022) - Piemontese, Luigi; Castelli, Giulio; Limones, Natalia; Grazio, Alice; Bresci, Elena
Abstract: Sand dams are simple and effective structures built across ephemeral riverbeds in arid/ semiarid regions to harvest water within sand pores and increase water availability and quality for rural communities. The complex morphological, hydrological, social, and economic conditions that make sand dams a beneficial tool for water resilience are largely influenced by the siting phase. Proper location of a sand dam can reduce communities' travel time to water points, reduce water conflicts, and increase food security through expansion of irrigated agriculture. On the other hand, a misplacement of sand dams can, at worst, increase disparities in water access and increase local conflicts. To approach a viable siting of sand dams, most projects are developed and delivered with the community through a bottom‐up approach. However, in the case of large‐scale projects, remote sensing and biophysical analysis are the dominant approach, leaving the socio‐economic component at the margins of the siting strategy and eventually affecting the benefits to local communities. In this paper, we propose a large‐scale participatory methodology to sand dams siting, which draws on mixed‐methods connecting the conventional top‐down biophysical analysis with bottom‐up participatory research. We first describe the generic approach developed for sand dams siting in Namibe, a semi‐arid region of Southwest of Angola, then we draw on our case to propose a generic approach to large‐scale participatory siting beyond Namibe.